21-4 Charlestown Street, Haymarket Square, 1864 - Unknown (Tufts Archival Research Center, 2005)
Elevated view looking north of (left to right) 21-4 Charlestown Street from Haymarket Square. Horse-drawn vehicles are outside many of the businesses. Many buildings have business signage affixed. In the foreground tracks for the horse railway can be seen and in the lower right corner a Bunker Hill horse railway car. Street later known as Washington Street North. 10 1/2 x 14 Photographs